Portfolio / Case Studies for Business English: Teacher's Guide - Howe Brian (Longman, 1995)
A collection of business case studies and activities for use during a business English course. Airline, Safety First, A Tale of Two Interests, Pause for Thought 1, New Formula Miracle, Pause for Thought 2, Fleet Street, Adventure Holidays International, Yamacom, Pause for Thought 3, Oxfam, A Sever Case of TSV, Pause for Thought 4, Auto Tech and the Electronic Map, Pause for Thought 5, Please Mr Banker, Agrichem International, Our Man in Nam Doa, Sea Link, Pause for Thought 6, Chun and the Desktop Computer, Tape Scripts.